Bibliometric analysis of the Iberoamerican scientific production related to taekwondo. (Revista horizonte, 2014)
Taekwondo is a martial art and Olympic sport that has experienced a significant growth in the number of practitioners worldwide. These developments have triggered the beginning and development of scientific activity around this discipline. In the other hand, bibliometric studies are methodological tools that have been recently applied to martial arts. In this way, the aim of the present study is to carry out a bibliometric analysis of Taekwondo scientific production published on the main Latin American databases. All articles related with taekwondo, extracted from Dialnet, SciELO and Redalyc databases, published in Spanish or Portuguese, regardless of the date of publication were included in this research. Data mining was conducted on March, 2014. The results indicate that 75 scientific articles were written from 1995 to 2013, presenting an irregular development along time. Training Theory and Psychology were the most studied areas; while Cuba, Spain, Brazil and Mexico are the most productive countries. The inclusion of Taekwondo as an Olympic sport has triggered its research in Latin American ountries, focusing on issues related with sports performance. In addition, the most productive countries seem to get better sport results in international Taekwondo competitions. To sum up, a relationship between scientific research and Latin American countries sport results might exist.